Rules of thumb for chemical engineers a manual of quick, accurate solutions to everyday process engineering problems - Branan, Carl; Elsevier Inc. ([United States] : Elsevier, 2006)
Book in cd-rom that contained information about chemical engineering, with 4 sections and 28 chapters
Title from title screen
Also available in text book
Systems requirement : 800{u00D7}600 pixels screen resolution, 256 colors, 128 MB RAM and operate on the Windows 98/SE/2000 or XP operating system or the MAC OS 10.2+ operating system, browser is JavaScript enabled, cookies enabled and has the'show images' checkbox enabled
Keywords: Chemical engineering -- Handbooks, manuals, etc..